Assessment of Information and Communication Technology for Selective Dissemination of Information and Current Awareness Services: A Case Study of University Libraries in the South-West Zone of Nigeria - Omeluzor, Saturday U.; Oyovwe-Tinuoye, Gloria O. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2017)
Objective – To assess the use of information and communication technology (ICT) for selective dissemination of information (SDI) and current awareness services (CAS) in university libraries in the South-West zone of Nigeria.Methods – A descriptive research design was adopted. The instrument used for data collection was a structured questionnaire administered to a population consisting of 379 librarians, with 353 usable questionnaires retrieved.Results – Findings revealed that most university libraries in the South-West zone of Nigeria do not use ICT in delivery of SDI and CAS. It is evident in this study that despite the known positive effects of ICT in library services, traditional methods were predominantly used for SDI and CAS to the library users. The study revealed that erratic Internet services, insufficient training, inadequate ICT skills, and low support for ICT were hindrances towards ICT use for SDI and CAS.Conclusions – The integration of ICT features in library services for the delivery of CAS and SDI has been a challenge in university libraries in South-West Nigeria. Only a few libraries and a low percentage of librarians had adopted the use of ICT in the delivery of CAS and SDI, while a larger number of libraries resorted to the use of traditional methods. The level of ICT literacy among the librarians in this study is low, as a higher percentage of librarians did not have adequate ICT skill to use available online resources on the Internet and other ICT tools to deliver SDI and CAS in South-West, Nigeria. This is not unconnected to the fact that the training and technical support received by the librarians is inadequate, and the level of support that academic libraries received from their university managements in South-West Nigeria in terms of funding for ICT development is inadequate, which led to low Internet services.